BUSINESS STRATEGY FORMULATION FOR SALES AND MARKETING CASE STUDY: SUPERBLOCK APARTMENT “X” IN JAKARTA - Lindawaty, Lindawaty (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
This study offers insights into how an apartment project “X” in Jakarta can utilize strategic business solutions to revitalize their sales and marketing efforts and overcome challenges in the market. The apartment market in Indonesia has been experiencing a decline in demand over the past five years, resulting in stagnant take-up rates, unchanged apartment prices, and a limited number of new apartment projects. To address this issue, the writer adapt the approach from Wheelen and Hunger (2010) on strategic management process framework, and performs svarious analysis, such as PESTEL, STP, Marketing Mix – 4P, and 3C. The analysis then serves as inputs for SWOT matrix and strategic initiative recommendation. Upon prioritization of the recommendation using the RICE scoring approach, the writer identified three quick wins initiatives that can be implemented within two months. The initiatives include (1) tailoring the messages to suit each market segment's product unique selling proposition and adding emotional benefits to the messages, (2) hiring a new promotion team with digital marketing capabilities, and (3) developing a special promotion for studio units that contribute the most to the stock.